Endoscopic Groin Lymphadenectomy With a Thigh Approach to Gynecologic Malignancies: A Retrospective Study With 5-Year Experience. Issue 2 (February 2015) - Li, Menghui; Wang, Shuzhen; Guo, Shuli; Zhang, Zhenyu
Abstract : Objectives: The objective of this study was to report a safe and feasible technique with endoscopic groin lymphadenectomy (EGL) through thigh approach in the treatment of different gynecologic malignancies. Study Design: Consecutive gynecological malignant patients proceeded to groin lymphadenectomy were treated by this technique over a 5-year period (2005 to 2010). Data regarding the surgical perioperative complications were recorded. Results: Eleven patients with 21 EGL were performed. Procedures included bilateral groin lymphadenectomy (n = 10) and left groin lymphadenectomy (n = 1). The median patient age and body mass index were 61 years and 25.2, respectively. The median operational time, which includes the dissection of both groins and the other procedures, was 210 minutes. The median blood loss was 200 mL. The median number of retrieved lymph nodes was 13 (range, 8–26), and all of these are histologically negative. No intraoperative complications occurred. One patient was noted in cutaneous cellulitis on the right side of the patient with clinical resolution 15 days after surgery. There were no perioperative mortalities. All the cutaneous scars were healed without wound breakdown. There were no perioperative mortalities. At the latest follow-up, all patients were completely satisfied with the cosmetic results. Conclusions: In this study, we first report EGL with a thigh approach in gynecologic malignancies; it is a safe and feasible technique, for groin nodal dissection, with low risks of morbidity of the skin and legs. A larger prospective study with long-term and survival analyses is warranted.